Internalization of Prophetic Values in Entrepreneurial Activities at the TMI Al-Amien Prenduan (Girls' Campus) Islamic Boarding School, Sumenep, Madura (2024–2025) - Ghina Shafiyyah; Moh. Wardi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to describe: (1) How is the application of the values of the Prophet Muhammad's character in entrepreneurship at the TMI Putri Al-Amien Prenduan Islamic boarding school? (2) How does the contribution of teachers/supervisors support the internalization of the Prophet Muhammad's character in entrepreneurship? To answer the question, the author uses a qualitative method. To describe the problems related to entrepreneurial activities at the TMI Putri Al-Amien Prenduan Sumenep Islamic Boarding School, because qualitative methods are used for observation, interviews, or document review, it facilitates direct contact between researchers and respondents. In theory, this study uses the FAST theory by Prof. Dr. Muhammad Syafii Antonio, Mec. The FAST theory is one of the concepts introduced by M. Syafii Antonio in his book